2017
DOI: 10.15446/ing.investig.v37n2.61822
|View full text |Cite
|
Sign up to set email alerts
|

Rapid generation of control parameters of Multi-Infeed system through online simulation

Abstract: Simulated Self-Generated - Particle Swarm optimization (SSG-PSO) toolbox that automatically generates PI control parameters very quickly in PSCAD is designed. This toolbox operates by utilizing transient simulation to evaluate objective function and converges the fitness values of objective function through PSO algorithm during run time simulation of Multi-infeed HVDC systems. Integral Square Error-Objective Function (ISE-OF) is used to accomplish the task. To make the toolbox faster, ranges are set for PSO ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Finally, it is suggested that all objective functions with soft computing techniques (SA or PSO) can be used for tuning purposes of controller, but selection of one OF is necessary. When comparing the optimized results of active-reactive powers of SSG-PSO (Aazim et al, 2017) and SG-SA parameters, responses of ISE-PSO are slightly better than ITAE-SA. From all these performances of system, it might be possible that PSO with ITAE-OF can produce surprising results.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Finally, it is suggested that all objective functions with soft computing techniques (SA or PSO) can be used for tuning purposes of controller, but selection of one OF is necessary. When comparing the optimized results of active-reactive powers of SSG-PSO (Aazim et al, 2017) and SG-SA parameters, responses of ISE-PSO are slightly better than ITAE-SA. From all these performances of system, it might be possible that PSO with ITAE-OF can produce surprising results.…”
Section: Resultsmentioning
confidence: 96%
“…The simplex algorithm is one of the convergence algorithms to obtain optimized control values, in order to produce the smallest fitness value of an objective function through a soft computing optimization technique. This technique is used in this work to get the optimal values of multiple PI (Aazim et al, 2017) controller parameters (Saravanakumar et al, 2015). Several runs are executed to minimize the fitness value of an objective function , as shown in Figure 1.…”
Section: Ifmentioning
confidence: 99%
See 3 more Smart Citations